2012
DOI: 10.1016/j.neuroscience.2012.08.039
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of angiotensin type 1a receptor-containing cells in the brains of bacterial artificial chromosome transgenic mice

Abstract: In the central nervous system, angiotensin II (AngII) binds to angiotensin type 1 receptors (AT1R) to affect autonomic and endocrine functions as well as learning and memory. However, understanding the function of cells containing AT1Rs has been restricted by limited availability of specific antisera, difficulties discriminating AT1 receptor-immunoreactive cells in many brain regions and, the identification of AT1R-containing neurons for physiological and molecular studies. Here, we demonstrate that an Agtr1a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
59
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(73 citation statements)
references
References 67 publications
11
59
3
Order By: Relevance
“…We examined expression patterns of both LEPR and AT 1A by using the NZ44-transgenic mouse, which expresses GFP inserted into the AT1a locus in a recombineered BAC transgene (11), and mice that conditionally Leptin contributes to the control of resting metabolic rate (RMR) and blood pressure (BP) through its actions in the arcuate nucleus (ARC). The renin-angiotensin system (RAS) and angiotensin AT 1 receptors within the brain are also involved in the control of RMR and BP, but whether this regulation overlaps with leptin's actions is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…We examined expression patterns of both LEPR and AT 1A by using the NZ44-transgenic mouse, which expresses GFP inserted into the AT1a locus in a recombineered BAC transgene (11), and mice that conditionally Leptin contributes to the control of resting metabolic rate (RMR) and blood pressure (BP) through its actions in the arcuate nucleus (ARC). The renin-angiotensin system (RAS) and angiotensin AT 1 receptors within the brain are also involved in the control of RMR and BP, but whether this regulation overlaps with leptin's actions is unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Further, several recent studies have indicated that AVP may play an important role in RAS-dependent hypertension (36). Based on data from BAC transgenic reporter mice, it is unlikely that magnocellular neurons of the PVN (or supraoptic nucleus) contain AT1R or AT2R (12,37), and the impact of Ang-II on AVP secretion may therefore be mediated by Ang-II receptor positive neural connections arising from upstream brain nuclei, such as the organum vasculosum of the lamina terminalis and subfornical organ (38,39). While the stimulatory effects of Ang-II on AVP secretion are likely mediated by the AT1R (34,35,40), several lines of evidence support the notion that activation of AT2R acts in opposition to this neurosecretory effect.…”
Section: Discussionmentioning
confidence: 99%
“…This antibody has been used to label EGFP expression in several different transgenic mouse lines (Gonzalez et al, 2012; Marques-Lopes et al, 2015; Marques-Lopes et al, 2014; Milner et al, 2010). In addition, this antibody does not label cells in brain tissue from mice lacking EGFP (Gonzalez et al, 2012). …”
Section: Methodsmentioning
confidence: 99%